2019
DOI: 10.1515/arh-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Drilling Fluid Rheology and Modeling of Thixotropic Behavior

Abstract: Drilling fluids perform a number of important functions during a drilling operation, including that of lifting drilled cuttings to the surface and balancing formation pressures. Drilling fluids are usually designed to be structured fluids exhibiting shear thinning and yield stress behavior, and most drilling fluids also exhibit thixotropy. Accurate modeling of drilling fluid rheology is necessary for predicting friction pressure losses in the wellbore while circulating, the pump pressure needed to resume circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Skadsem et al [18] reported that their steady rheological measurements (with a smooth bob and container walls) were overall well represented by the Herschel-Bulkley model, except at low shear rates probably due to apparent slip effects or short measurement time. In particular, the model overestimated shear stresses at shear rates lower than ca.…”
Section: Herschel-bulkley Modelmentioning
confidence: 94%
“…Skadsem et al [18] reported that their steady rheological measurements (with a smooth bob and container walls) were overall well represented by the Herschel-Bulkley model, except at low shear rates probably due to apparent slip effects or short measurement time. In particular, the model overestimated shear stresses at shear rates lower than ca.…”
Section: Herschel-bulkley Modelmentioning
confidence: 94%
“…Vajargah et al [12] presented experimental tests for automated calculations of drilling fluids' properties with the use of a pipe viscometer. Skadsem et al [13] reported a detailed rheological characterization of a water-based drilling fluid and an invert emulsion oil-based drilling fluid and analysed the shear rate step change measurements using a structural kinetics thixotropy model. In terms of successful industrial examples, Stock et al [14] provided a good overview and introduction of industrial control systems and devices used for drilling fluids' propterty measurements and monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The rheological models are essential for drilling mud rheology analysis because they are employed to stimulate the behaviour of drilling mud under different dynamic conditions (Skadsem et al 2019). The rheological models can help us to predict and estimate the following applications/ behaviour (Wiśniowski et al 2020):…”
Section: Rheological Modellingmentioning
confidence: 99%